Preparation, Characterization of Silver-Nanoparticles from Seed Coat Exudates of Celastrus paniculatus Willd. and Their Bactericidal and Biofilm Inhibition Effects (International Journal of Pharmaceutical Sciences and Drug Research, 2019)
We are reporting a novel approach for preparing silver nanoparticles with seed coat exudates of Celastrus paniculatus Willd, a medicinal plant traditionally used for the treatment of skin diseases, fever, leprosy and neurological disorders. HPTLC study revealed that aqueous, soluble seed coat exudates contain phenolics, alakaloids and flavonoids. The formation, crystalline nature and morphology of the nanoparticles were identified by UV–Vis spectroscopy, X-ray Diffraction (XRD) analysis, Transmission Electron Microscopy (TEM) and selected-area electron diffraction (SAED). Functional group stretching of aqueous soluble extracts was identified by using FTIR. Results revealed that nanosilver particles are spherical, range in size from 10 to 82 nm and crystalize in face-centered cubic structures. Surface-enhanced Raman spectra analysis showed that AgNP are capped with bioactive molecules from exudates and that they may act as precursors of the reduction of silver nitrate from the metallic state (Ag+) to the atomic state (Ag0). We also examined the minimal inhibitory concentration for bacteria Escherichia coli and Bacillus subtilis using a resazurin color assay. Nanosilver strongly inhibited the bacterial growth, leading to MIC values of 40µg/ml and 60µg/ml for the bacteria, respectively. The colony screening method and inhibition kinetics of biofilm formation in the Klebsiella pneumoniae strain were also studied using the tube method and a quantitative microplate assay. SEM analysis and quantification of the EPS revealed a fivefold decrease in concentration in treated compared to untreated. The inhibition response was duly reflected in SEM images.